Expression of innate immunity genes in human hematopoietic stem/progenitor cells – single cell RNA-seq analysis - Jarczak, Justyna; Thetchinamoorthy, Kannathasan; Wierzbicka, Diana; Bujko, Kamila; Ratajczak, Mariusz Z.; Kucia, Magdalena (Frontiers in Immunology, 2025)
BackgroundThe complement system expressed intracellularly and known as complosome has been indicated as a trigger in the regulation of lymphocyte functioning. The expression of its genes was confirmed also in several types of human bone marrow-derived stem cells: mononuclear cells (MNCs), very small embryonic-like stem cells (VSELs), hematopoietic stem/progenitor cells (HSPCs), endothelial progenitors (EPCs) and mesenchymal stem cells (MSCs). In our previous studies, we demonstrated the expression of complosome proteins including C3, C5, C3aR, and cathepsin L in purified HSPCs. However, there is still a lack of results showing the expression of complosome system elements and other immunity-related proteins in human HSPCs at the level of single cell resolution.MethodsWe employed scRNA-seq to investigate comprehensively the expression of genes connected with immunity, in two populations of human HSPCs: CD34+Lin-CD45+ and CD133+Lin-CD45+, with the division to subpopulations. We focused on genes coding complosome elements, selected cytokines, and genes related to antigen presentation as well as related to immune regulation.ResultsWe observed the differences in the expression of several genes e.g. C3AR1 and C5AR1 between two populations of HSPCs: CD34+LinCD45+ and CD133+Lin-CD45+ resulting from their heterogeneous nature. However, in both kinds of HSPCs, we observed similar cell subpopulations expressing genes (e.g. NLRP3 and IL-1β) at the same level, which suggests the presence of cells performing similar functions connected with the activation of inflammatory processes contributing to the body's defense against infections.DiscussionTo our best knowledge, it is the first time that expression of complosome elements was studied in HSPCs at the single cell resolution with the use of single cell sequencing. Thus, our data sheds new light on complosome as a novel regulator of hematopoiesis that involves intracrine activation of the C5a-C5aR-Nlrp3 inflammasome axis.